A New Crayfish of the Genus Cambarus (Decapoda: Cambaridae) From the Flint River Drainage in Northern Alabama and South Central Tennessee, U.S.A. - Jones, Danny R. (Zootaxa, 2016)
Examination of specimens of the crayfish species Cambarus (Hiaticambarus) longirostris and two recently described crayfish revealed the existence of an undescribed species from the Flint River watershed in northern Alabama and southern Tennessee. Cambarus (Hiaticambarus) lentiginosus differs from C. longirostris, C. (Hiaticambarus) andersoni, and C. (Hiaticambarus) diupalma in aspects of carapace and chela morphology and pigmentation pattern. Cambarus (H.) lentiginosus possesses a median carina on the dorsal surface of the acumen of the rostrum, a distinctly enlarged tubercle near the base of the opposable surface of the dactyl, and a speckled pigmentation pattern over a light base color; these characters are lacking in other known Hiaticambarus species. The known range of the species is restricted to the Flint River watershed. Cambarus (H.) lentiginosus is considered Endangered using American Fisheries Society conservation categorization.